DINAMIKA KONSTITUSI DAN PERUBAHAN HUKUM TATA NEGARA SEBUAH TINJAUAN PERUBAHAN KONSTITUSI DI ERA DIGITAL - Rasji Rasji; Grace Avianti; Kent Edward (Peneliti.net, 2023)
The development of digital technology has had a significant impact on the dynamics of constitutions and the changes in constitutional law in the modern era. This article aims to provide an overview of constitutional changes occurring in the context of the digital era. A country's constitution serves as the legal foundation governing its system of government and the rights of its citizens, and constitutional changes in the digital era involve new aspects that need to be considered. In the digital era, information technology has transformed the way people communicate, interact, and participate in the process of public policy formation. The internet and social media have become important means for individuals to express their aspirations and influence political decision-making processes. This has led to demands for constitutional changes to accommodate these new developments. Technological advancements also present new challenges to the protection of human rights and privacy. In the digital era, safeguarding freedom of speech, freedom of expression, and access to information has become more complex. Constitutions must be able to adapt to these changes in order to safeguard citizens' freedoms. However, constitutional changes in the digital era also pose various challenges. Careful regulation is needed to strike a balance between freedom of expression and the protection of issues such as harmful content dissemination, cybercrime, and privacy violations. In this context, an overview of constitutional changes in the digital era becomes crucial to ensure that constitutional law remains relevant and provides adequate protection in the face of evolving technological challenges. The process of constitutional change should involve broad public participation and thoughtful consideration to achieve the appropriate balance between technological innovation and the protection of citizens' rights.